2006
DOI: 10.1063/1.2192577
|View full text |Cite
|
Sign up to set email alerts
|

Ferromagnetism in 200-MeV Ag+15-ion-irradiated Co-implanted ZnO thin films

Abstract: Structural, electrical resistivity, and magnetization properties of 200-MeV Ag+15-ion-irradiated Co-implanted ZnO thin films are presented. The structural studies show the presence of Co clusters whose size is found to increase with increase of Co implantation. The implanted films were irradiated with 200-MeV Ag+15 ions to fluence of 1×1012ions∕cm2. The Co clusters on irradiation dissolve in the ZnO matrix. The electrical resistivity of the irradiated samples is lowered to half. The magnetization hysteresis me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(21 citation statements)
references
References 18 publications
2
18
1
Order By: Relevance
“…Recently high energy electronic excitation due to swift heavy ion (SHI) irradiation has been considered as a great tool for the modifications in the structural, optical and magnetic properties of various materials in bulk as well as thin films [21,22]. Formation of single phase Co-implanted ZnO thin films using SHI irradiation has been reported by Angadi et al [23]. It has been shown earlier also that Modifications in the structural and optical properties of 100 MeV Ni 7+ ions irradiated cobalt doped ZnO thin films (Zn 1Àx Co x O, x = 0.05) prepared by sol-gel route were studied.…”
Section: Introductionmentioning
confidence: 98%
“…Recently high energy electronic excitation due to swift heavy ion (SHI) irradiation has been considered as a great tool for the modifications in the structural, optical and magnetic properties of various materials in bulk as well as thin films [21,22]. Formation of single phase Co-implanted ZnO thin films using SHI irradiation has been reported by Angadi et al [23]. It has been shown earlier also that Modifications in the structural and optical properties of 100 MeV Ni 7+ ions irradiated cobalt doped ZnO thin films (Zn 1Àx Co x O, x = 0.05) prepared by sol-gel route were studied.…”
Section: Introductionmentioning
confidence: 98%
“…These predictions largely boosted intensive experimental activities on transition metal doped GaN and * Electronic address: S.Zhou@fzd.de ZnO. A large number of research groups have reported the experimental observation of ferromagnetism in TM (from Sc to Ni) doped ZnO [7,8,9,10,11,12,13,14,15] fabricated by various methods including ion implantation. For a comprehensive review, see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Ion beam gives a better alternative for converting the amorphous Si to crystalline Si by irradiation at temperatures up to a few hundred degree centigrade. Low-energy irradiation upto a few MeV has been exploited 67 for the recrystallisation process. In this energy region, either the nuclear energy loss dominates or both the electronic and nuclear energy loss are of comparable value.…”
Section: Ion Beam Induced Epitaxial Crystallisationmentioning
confidence: 99%